Use the quadratic formula to find the solution to the quadratic equation given below. X^2-x+1/4=0

Question

Use the quadratic formula to find the solution to the quadratic equation given
below.
X^2-x+1/4=0

in progress 0
Tài Đức 3 months 2021-07-24T17:51:21+00:00 1 Answers 5 views 0

Answers ( )

    0
    2021-07-24T17:52:53+00:00

    Answer:

    \displaystyle x=\frac{-1}{2}

    General Formulas and Concepts:

    Pre-Algebra

    Order of Operations: BPEMDAS

    1. Brackets
    2. Parenthesis
    3. Exponents
    4. Multiplication
    5. Division
    6. Addition
    7. Subtraction
    • Left to Right

    Algebra I

    • Standard Form: ax² + bx + c = 0
    • Quadratic Formula: \displaystyle x=\frac{-b \pm \sqrt{b^2 - 4ac}}{2a}

    Step-by-step explanation:

    Step 1: Define

    Identify

    x² + x + 1/4 = 0

    ↓ Compare to Standard Form

    a = 1, b = 1, c = 1/4

    Step 2: Solve for x

    1. Substitute in variables [Quadratic Formula]:                                                  \displaystyle x=\frac{-1 \pm \sqrt{1^2 - 4(1)(\frac{1}{4})}}{2(1)}
    2. [√Radical] Evaluate exponents:                                                                       \displaystyle x=\frac{-1 \pm \sqrt{1 - 4(1)(\frac{1}{4})}}{2(1)}
    3. [√Radical] Multiply:                                                                                           \displaystyle x=\frac{-1 \pm \sqrt{1 - 1}}{2(1)}
    4. [√Radical] Subtract:                                                                                          \displaystyle x=\frac{-1 \pm \sqrt{0}}{2(1)}
    5. [√Radical] Evaluate:                                                                                         \displaystyle x=\frac{-1 \pm 0}{2(1)}
    6. Simplify:                                                                                                             \displaystyle x=\frac{-1}{2(1)}
    7. Multiply:                                                                                                             \displaystyle x=\frac{-1}{2}

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )